2010
DOI: 10.1007/s00216-010-3568-0
|View full text |Cite
|
Sign up to set email alerts
|

FT-Raman spectroscopic analysis of pigments from an Augustinian friary

Abstract: The Raman spectroscopic analysis of several stone samples with applied red pigments obtained from an archaeological excavation of an Augustinian friary discovered during the construction of an extension to Hull Magistrates Court in 1994 has revealed a surprising diversity of composition. Cinnabar, red lead and haematite have all been identified alone or in admixture; the cinnabar is exceptional in that it has only been found heavily adulterated with red ochre and red lead, as the other two pigments are found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The peaks below 200 cm −1 were not detected due to limitations associated with the model the Raman instrument employed. According to the literature, the application of the gilding over the ground layer containing the mixture of vermilion with red lead has a rich historical background . Vermilion, red lead, or other red iron oxide pigments were commonly added into the gilding adhesive with the aim of enhancing the colour of the gold.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks below 200 cm −1 were not detected due to limitations associated with the model the Raman instrument employed. According to the literature, the application of the gilding over the ground layer containing the mixture of vermilion with red lead has a rich historical background . Vermilion, red lead, or other red iron oxide pigments were commonly added into the gilding adhesive with the aim of enhancing the colour of the gold.…”
Section: Resultsmentioning
confidence: 99%
“…The pigments of the polychrome limestone sculpture ‘Las tres generaciones’ (Cathedral's Museum of Santiago de Compostela, Spain) were characterized by Prieto et al Edwards et al reported a study on pigments on stone samples from an Augustinian friary. He et al performed a multianalytical study of the polychromy in the Guangyuan Thousand‐Buddha Grotto, ‘the museum of painted stone sculpture’: the complex analysis suggests atacamite and malachite as true green pigments.…”
Section: Introductionmentioning
confidence: 99%
“…The relative Raman spectra acquired on different points of black samples evidenced the carbon‐containing compound presence by means of the characteristic two broad features G (graphitic, 1580 cm –1 ) and D1 (disorder, 1320 cm –1 ), respectively assigned to crystalline graphite and to structural disorder in the graphitic structure (Fig. S4).…”
Section: Resultsmentioning
confidence: 99%